INTERNAL CONTROL AS A TOOL TO REDUCE TAX CONTINGENCIES - Benítez Alderete, Richard; David Cabrera Benítez, Edgar; María Patricia Mereles Sosa, Daysi (Revista Gênero e Interdisciplinaridade, 2023)
The research presented is entitled “Internal control as a tool to reduce tax contingencies”, it aims to describe the influence of internal control in commercial companies in Ciudad del Este in terms of risk reduction in compliance with their obligations. tax. 15 company accountants have been taken as a sample, corresponding to 50% of the population. It is concluded that internal control is an effective method if the taxpayer, whether it is a company or an individual, complies with their tax obligations.